Characterization of relative projectives and relative injectives - Ccolque Taipe, Felipe Clímaco (2020)
In this article, given a ring homomorphism F: R -->S, the relative projectives and relative injectives are characterized. An S - module is relative projective if and only if it is retract of SxR C; An S -  module is relative injective if and only if it is retract of HomR(S;C).